Evolution and Dynamics of the Australian Plate 2003
DOI: 10.1130/0-8137-2372-8.157
|View full text |Cite
|
Sign up to set email alerts
|

The hot southern continent: heat flow and heat production in Australian Proterozoic terranes

Abstract: Available surface heat-flow measurements from Australian Proterozoic terranes (83 ± 18 mWrrr 2 ) are significantly higher than the global Proterozoic average of -50 mWnrr 2 . Seismic evidence for the presence of relatively cool mantle together with the lack of evidence for neotectonlc processes normally associated with thermal transients suggests that anomalous heat flow must reflect crustal radiogenic sources (U,Th and K).This is supported by a compilation of more than 6000 analyses from 455 individual granit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 29 publications
2
91
0
Order By: Relevance
“…Four of the clasts give high values between 4.0 and 7.5 µW m −3 , which are similar to global occurrences of crust characterized by high heat production (Mareschal and Jaupart, 2013;Jaupart et al, 2016) and exemplified by the Central Australian Heat Flow Province (Neumann et al, 2000;Sandiford and McLaren, 2002;McLaren et al, 2003). Nonetheless, all but two of the samples in this suite have heat production less than the mean for the CAHFP (4.6 µW m −3 ).…”
Section: Heat Productionmentioning
confidence: 70%
See 2 more Smart Citations
“…Four of the clasts give high values between 4.0 and 7.5 µW m −3 , which are similar to global occurrences of crust characterized by high heat production (Mareschal and Jaupart, 2013;Jaupart et al, 2016) and exemplified by the Central Australian Heat Flow Province (Neumann et al, 2000;Sandiford and McLaren, 2002;McLaren et al, 2003). Nonetheless, all but two of the samples in this suite have heat production less than the mean for the CAHFP (4.6 µW m −3 ).…”
Section: Heat Productionmentioning
confidence: 70%
“…As a group they are distinctly different from the regional pattern shown by anomalously warm Proterozoic crust in central Australia with average q o = 80 mW m −2 (McLaren et al, 2003), which has been suggested to extend across the Wilkes Land margin of Antarctica based on Gondwana supercontinent reconstructions (Carson et al, 2014;Aitken et al, 2014). Despite general age similarities among some of the clast population with parts of the Gawler Craton, and basement age correlations that indicate continuity of Mawson-type crust into the Wilkes sector of East Antarctica (Goodge and Fanning, 2016), the proxy heat production determinations and heat flow estimates provided here suggest that central portions of the East Antarctic ice sheet are underlain by stable continental crust with quite normal thermal properties represented by average values of heat production of about 2.5 µW m −3 and heat flow of about 50 mW m −2 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Amadeus and McArthur basins; Figs 6 and 7). In addition, in central Australia the crustal contribution to heat flow is about twice that expected of the global-average continental crust (McLaren et al 2003). This is a direct result of a higher than average concentrations of crustal radiogenic elements U and Th (McLaren et al 2003), leading to 4 He.…”
mentioning
confidence: 81%
“…In addition, in central Australia the crustal contribution to heat flow is about twice that expected of the global-average continental crust (McLaren et al 2003). This is a direct result of a higher than average concentrations of crustal radiogenic elements U and Th (McLaren et al 2003), leading to 4 He. More restricted areas with high surface heat flow are outboard of the Browse and Perth basins (Cull and Conley 1983); interestingly, the first-order heat flow is relatively low and fairly constant throughout the North West Shelf (Cull and Conley 1983).…”
mentioning
confidence: 81%